Emotional and Social Competence in School Beginners: An Intervention Programme for Teachers and Therapists - Deacon, Elmarí; Rensburg, Esmé Van (American Journal of Education and Learning, 2018)
This programme was developed to enhance emotional and social competence in a group of South-African school beginners (aged 5 – 6 years). The programme addressed themes such as emotions, friendship, emotional communication, internal and external emotions, self-regulation, problem solving, self-concept, self-confidence, moral development and the successful student. After the intervention, there were practically significant differences in internalization of problems and social competence in general within the experimental group, as well as improvement in practical reasoning.